(NfONETIKA FRANCUZSKOGO QZYKA (B/s - (NgORDINA(B, (NmIRRA wENIAMINOWNA(B.s; (NlENINGRADSKIJ GOSUDARSTWENNYJ UNIWERSITET IM(B. (Na(B.(Na(B. (NvDANOWAs ((NlENINGRAD (B:s (Nlgu(B,s, 1973)
(NsPISOK LIT(B.: (NS(B. 202-206s
(NlENINGR(B. (NGOS UN(B-(NT IM a(B.(Na(B. (NvDANOWAs
Keywords: (NfRANCUZSKIJ QZYK (B- (NfONETIKAs